Multiple complications of advanced IPF in an individual patient presentation. Issue 4 (24th March 2023) - Ledger, Thomas; Braude, Stanley
Abstract: We report a patient with advanced idiopathic pulmonary fibrosis (IPF), who in a single presentation experienced three complications of the disease: an acute exacerbation, spontaneous pneumomediastinum, and platypnoea‐orthodeoxia syndrome. Despite there being no definitive evidence‐based treatment for an acute exacerbation, we report a marked improvement with high‐dose steroids. This case also highlights the importance in IPF patients of considering pneumomediastinum as a cause of non‐cardiac chest pain, as well as platypnoea‐orthodeoxia in those with positional dyspnoea. Abstract : We report a patient with advanced idiopathic pulmonary fibrosis (IPF), who in a single presentation experienced three complications of the disease: an acute exacerbation, spontaneous pneumomediastinum, and platypnoea‐orthodeoxia syndrome. Despite there being no definitive evidence‐based treatment for an acute exacerbation, we report a marked improvement with high‐dose steroids. This case also highlights the importance in IPF patients of considering pneumomediastinum as a cause of non‐cardiac chest pain, as well as platypnoea‐orthodeoxia in those with positional dyspnoea.